Fall Meeting of the Society of Petroleum Engineers of AIME 1971
DOI: 10.2118/3530-ms
|View full text |Cite
|
Sign up to set email alerts
|

A New Practical Approach to Rotary Drilling Hydraulics

Abstract: American Institute of Mining, Metallurgical, and Petroleum Engineers, Inc. This paper was prepared for the 46th Annual Fall Meeting of the Society of Petroleum Engineers of AIME, held in New Orleans, Oct. 3–6, 1971. Permission to copy is restricted to an abstract of not more than 300 words. Illustrations may not be copied. The abstract should contain conspicuous acknowledgment of where and by whom the paper is presented. Publication elsewhere after publication in the JOURNAL OF presented. Public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1974
1974
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The expected bit life is given by (19) where m is the slope of a plot of parasitic pressure drop vs flow rate on log-log paper. Note that by operating in accordance with Eq.…”
Section: Optimum Hydra Uliesmentioning
confidence: 99%
See 2 more Smart Citations
“…The expected bit life is given by (19) where m is the slope of a plot of parasitic pressure drop vs flow rate on log-log paper. Note that by operating in accordance with Eq.…”
Section: Optimum Hydra Uliesmentioning
confidence: 99%
“…Theoretical considerations indicate a value of 1.8 for m. However, Scott has recently reported measuring m values as low as 1.0. 19 An evaluation of the proposed optimization scheme has indicated that in many cases a considerable (The drillability parameter, which is based on Eq. 1, is somewhat analogous to the lCd-exponent" developed by Jorden and Shirley 11 using a more simplified penetration rate equation.)…”
Section: Optimum Hydra Uliesmentioning
confidence: 99%
See 1 more Smart Citation